The production of bio oil through batch pyrolsis process - Mohd Taufik, Mohamd Tahir (2009)
Energy demand is increasing continuously due to rapid growth in population and industrialization development. The major energy demand is provided from the conventional energy sources such as coal, oil, natural gas, etc. Two major problems, which every country is facing with these conventional fuels, are depletion of fossil fuels and deterioration of environment. Pyrolysis of biomass will be one of the alternative ways to encounter this problem. The pyrolysis of palm-oil industrial waste was investigated in a static batch reactor is. The effect of pyrolysis parameter on the product yields and composition were investigated. PKS was pyrolysed at moderate range of temperatures of 200˚C, 300˚C, 400˚C, 500˚C and 600˚C. The effects of various temperatures towards the yield of pyrolysis process of palm kernels were investigated. The compositions and properties of the pyrolytic oils and solid chars are determined with respect to pyrolysis temperatures. The static batch reactor shows that the temperature of 400 ˚C gives the highest percentage of PKS bio-oil yield which attributes to 37.2 %. EFB with sample length of L < 1 mm, 1-5 mm, 5-10 mm, L > 10 mm were pyrolysed at constant temperature of 400 ˚C. The highest yield of the bio oil for the empty fruit bunches is obtained at the range of length between 5-10 mm whish attribute to 39.525 wt%. Preliminary experiment was conducted using thermogravimetric analyzer (TGA) to determine the volatility, ash content, moisture and fixed carbon. The functional groups of the product which is bio oil are identified by using Fourier Transform infrared spectrometer (FTIR). The chemical characterization studies show that the bio oil obtained from the palm kernels has the potential to be a valuable source renewable fuel and as feedstock for specialty of chemicals.